The Effect of Profitability Towards Financial Distress - Thomson Sitompul; Debra Juneta; Muhammad Kifli Siregar (Universitas Pelita Harapan, 2026)
This research distinguishes itself from previous studies by using data from 2017 to 2023. This study was conducted for the purpose to know the effect of profitability towards financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017 – 2023, data from 226 population. Data were collected using purposive sampling method, selected 46 companies, and 322 unit of observations as samples. The data analysis method in this research is multiple linear regression test and SPSS. This research has 1 dependent variable, 1 main independent variable, and 4 control variables. The dependent variable is financial distress which is calculated using Altman Z-Score model. The independent variable is profitability which is calculated with return on assets (ROA). The control variables are leverage, which is calculated using debt to asset ratio (DAR), liquidity is calculated using current ratio (CR), activity calculated using assets turnover, and firm size is calculated using natural logarithm of total asset. The result of this study shows that profitability and activity have significant and positive effect towards financial distress, leverage has a significant and negative effect towards financial distress, liquidity and firm size have no significant effect towards financial distress.